Use of Psychotropic Medications and Illegal Drugs, and Related Consequences Among French Pharmacy Students – SCEP Study: A Nationwide Cross-Sectional Study - Balayssac, David; Pereira, Bruno; Darfeuille, Maxime; Cuq, Pierre; Vernhet, Laurent; Collin, Aurore; Vennat, Brigitte; Authier, Nicolas (Frontiers in Pharmacology, 2018)
Background: The use of psychotropic medications and illegal drugs is a worldwide public health issue, leading to addiction, psychiatric and somatic disorders, and death. Pharmacy students are more exposed to psychotropic medications than other students (non-medical), which could lead to an overuse. The main objective of this study was to assess the prevalence of psychotropic drug use (medications and illegal drugs) by French pharmacy students, by carrying out a nationwide cross-sectional study. The relation of these medications and illegal drug use with several comorbidities and academic achievement was also assessed. Methods: This online survey was performed by emails sent to all French pharmacy faculties over a period of 66 days (March 16, 2016 to May 20, 2016). The survey assessed the prevalence of uses of psychotropic medications and illegal drugs during the last 3 months. These uses were compared to student characteristics (personal and university) and comorbidities (anxiety, depression, stress and fatigue). Results: Of the 2,609 questionnaires received, 2,575 were completed and useable for the analysis. Among French pharmacy students and during the 3 last months, 9.4% have used psychotropic medications, 21.5% illegal drugs and 3.3% both psychotropic medications and illegal drugs. Psychotropic medications were used in the cases of a medical prescription (49.0%), a self-medication (42.4%) or a non-medical intent (26.3%). Stress scores of the last 7 days were higher for psychotropic medication users compared to non-users and illegal drug users. Proportions of anxiety and depression at the time of answer were higher for psychotropic medication users than for non-users and illegal drug users. Fatigue scores of the last 7 days were lower for illegal drug users compared to non-users and self-medicated students. Annual average marks of the last year, attendance and perception of study difficulty were lower for illegal drug users than for non-users. Conclusion: French pharmacy students were less exposed to psychotropic medications and illegal drugs than the general French population. However, in comparison to other students in other countries, the use of psychotropic medications seemed to be lower, but with a proportionally higher use of anxiety/sedative medications and a lower use of opioid medications.